Translation and cross-cultural adaptation of an instrument designed for the assessment of quality of life in orthognatic patients - Adriana Monteiro de Araújo; José Augusto Mendes Miguel; Eveline Coutinho Baldoto Gava; Branca Heloisa de Oliveira (Dental Press Editora, 2013)
INTRODUCTION: The Orthognathic Quality of Life Questionnaire (OQLQ) was developed in 2000 and validated in 2002, aiming at assessing the impact and the benefits of orthosurgical treatment on patients' quality of life. OBJECTIVE: Cross-culturally translate into Brazilian Portuguese and back-translate into English a quality of life instrument, assuring maintenance of its properties. METHODS: At first, equivalence of concepts and items was discussed by a group of specialists who scrutinized all questionnaire items. Additionally, four patients in need of orthosurgical treatment were interviewed by means of the focus group methodology. Relevance of the questionnaire items was assured prior to its translation which was carried out by two translators who worked independently. Both translations were tested in 20 patients and then consolidated. The consolidated questionnaire version was back-translated into English by two translators who worked independently, and the consolidated back-translation was assessed by the authors of the original questionnaire as well as by the researchers. RESULTS: The OQLQ was translated into Brazilian Portuguese. This translation was tested in a pilot study comprising 12 patients, aged between 16 and 34 years old. CONCLUSION: The OQLQ Brazilian Portuguese translation proves to be an appropriate instrument to access the impact of dentofacial deformities on the quality of life of patients in the Brazilian public health system and who are in need of orthosurgical treatment.